Sympathetic skin response and R–R interval variation in the assessment of clinical remission of bipolar disorder. (30th March 2016) - Wang, Xinling; Cao, Ping; Xu, Luoyi; Cai, Liqiang; Zhang, Lei; Feng, Rui; Jiang, Hong; Chen, Wei
Abstract: For our retrospective study, we chose patients who met the inclusion criteria for bipolar disorder (BD) according to the ICD-10. We conducted correlation analyses between scale scores and SSR and RRIV values before and after 1 year ±1 month of treatment. Our results suggest that the feet SSR latency and R % can be used as an indicator of clinical BD remission. The scales have high sensitivity and low specificity in assessing BD remission. Highlights: Autonomic nervous system activity reflects remission of bipolar disorder (BD). Scales measuring BD remission have high sensitivity, low specificity. RRIV at rest can be used to evaluate the therapeutic efficacy of BD treatments.